(untitled) (Journal of Surgical Sciences, 2019)
Background: The study was undertaken to validate the efficacy of Delorme’s procedure as the treatment modality of choice for full-thickness rectal prolapse. Materials and Methods: In this study, results of Delorme’s procedure for full-thickness rectal prolapse were assessed retrospectively. 14 patients with full-thickness rectal prolapse who were operated on with Delorme’s procedure between January 2010 and October 2013 in the department of Colorectal surgery, Bangabandhu Sheikh Mujib Medical University were included in the study. Results: There were 8 males with mean age of 32.62 years (range 15-70) and 6 females with mean age of 26 years (range 12-70 ).The mean operative time was 65±4.5 minutes (range 60-90); there was no mortality and blood loss was minimal. Mean hospital stay was 3.5 days (2-6 days). Outcomes of the procedure were satisfactory and no patient reported recurrence of the disease in the follow up period.Delorme’s procedure, especially in younger patients, is a relatively safe and effective treatment and should not be restricted to older frail patients. This procedure may not be suitable for recurrent cases Delorme’s procedure, especially in younger patients, is a relatively safe and effective treatment and should not be restricted to older frail patients. This procedure may not be suitable for recurrent cases. Conclusion: Delorme’s operation is a safe and effective treatment for complete rectal prolapse in patients of all age groups. Journal of Surgical Sciences (2015) Vol. 19 (1) : 21-24